Synchronization criteria for singular complex networks with Markovian jump and time-varying delays via pinning control. (August 2018) - Ma, Yuechao; Ma, Nannan; Chen, Lin
Abstract: This paper makes a study on the problem of synchronization for singular complex networks with Markovian jumping parameters and mixed time-delays. The system consists of N nodes which switch from one mode to another according to a Markovian chain with known transition probability. Based on the strategies of pinning control, the singular complex networks are synchronized. A new type of criterion for synchronization can be obtained by means of utilizing the appropriate Lyapunov–Krasovskii function, the linear matrix inequality (LMI) approach, stochastic analysis techniques and the convexity of matrix functions. Finally, simulation examples are employed to demonstrate the effectiveness of the proposed method.